Concurrent presentation of erythrodermic lichen planus and squamous cell carcinoma: Coincidence or malignant transformation? - Neema M Ali; Ramesh Bhat; Shwetha B Rao (Wolters Kluwer Medknow Publications, 2015)
Lichen planus is a common papulosquamous disorder affecting about 1-2% of the population, neoplastic transformation of cutaneous lichen planus lesions occurs very rarely. A 40 year old female patient presented with a 1 year history of developing multiple, itchy, pigmented lesions over both lower legs which gradually spread to involve the whole body. A few tense bullae were seen on the extremities. An erythematous fleshy lesion was seen on the upper aspect of the left buttock. Skin biopsy from a plaque on the right forearm showed features suggestive of lichen planus. Skin biopsy of a bullae showed a sub epidermal bulla filled with a mixed inflammatory infiltrate. Direct immunofluorescence revealed no immunoreactants along the basement membrane zone. A diagnosis of erythrodermic lichen planus with bullous lichen planus was made. Biopsy of fleshy lesion of left buttock revealed a moderately differentiated squamous cell carcinoma. Erythrodermic lichen planus with bullous lesions and secondary squamous cell carcinoma; these occurences in a single patient is extremely rare and has not been previously reported to the best of our knowledge.